PROMOTING STUDENTS’ SPEAKING SKILL IN VIRTUAL LEARNING: UTILIZING YOUTUBE AS MEDIA AND VIDEO POSTING - Zaitun, Zaitun; Salsabila, Rana (English Community Journal, 2022)
This research study aimed to present the investigation of utilizing YouTube as learning media for students to access speaking videos and posting those speaking videos on social media in promoting students’ speaking skill in virtual instruction. A mixed-method of qualitative and quantitative approaches is applied in this study. In collecting the data, three instruments were used, namely observation, interview and documents of students’ speaking test results. The class observation revealed that the students learned more in understanding how to perform speaking better from the speaking videos they had watched from YouTube. The average score the students gained from their videos uploading on Instagram after the course (4.12) was higher than that in the pre-test (2.40). These scores were assessed based on speaking scoring rubric of Brown’s (2001). From the uploaded videos observation (watching) of the students, it could be seen that their speaking performance improved from their initial videos to the second ones in which they were more confident, accurate, fluent and comprehensive. From the interview to the lecturer, it was understood that the students enjoyed watching the videos and they became more motivated to learn and practice their speaking skill. Besides, in order to post their best speaking videos, they put their best efforts to perform well since they realized that their videos would be watched by myriad numbers of people. Therefore, this research work confirmed that utilizing YouTube as media and posting videos on social media as activities applied in virtual speaking class promoted students’ speaking skill.